Sociological Analysis of Peaceful Coexistence in Kurdish Society - Saber, Nian Namik; Mohamed Rashid, Sherine Ibrahim (Journal of Tikrit University for Humanities, 2020)
This research is concerned with the study of peaceful coexistence in Kurdish society. The concept of coexistence is based on the awareness of individuals or groups that have different religious, racial or intellectual identities and the recognition that this is a difference that should not lead to violent conflicts between individual or group bearers. Hence, the present research deals with the issue of peaceful coexistence as a means of perpetuating and sustaining peace in Kurdish society